2016
DOI: 10.5664/jcsm.5400
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Milnacipran on Sleep Disturbance in Fibromyalgia: A Randomized, Double-Blind, Placebo-Controlled, Two-Way Crossover Study

Abstract: Objective: This study examined the effects of milnacipran on polysomnographic (PSG) measures of sleep and subjective complaints in patients with fibromyalgia and disturbed sleep. Methods: This was a single-site, double-blind, placebo-controlled, two-period crossover PSG study. Eligible subjects (aged 28-72 y) were randomized (1:1) to milnacipran (100 mg/d) or placebo for crossover period 1, and vice versa for period 2. Each crossover period comprised a dose-escalation and dose-maintenance phase, with a 2-w tap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…We excluded 22 studies in total: we excluded nine in the 2013 review (Branco 2011; Chappell 2009b; Dwight 1998; Goldenberg 2010; Hsiao 2007; Mease 2010; Saxe 2012; Sayar 2003; NCT00369343) (total corrected in this review), and 13 additional studies for the update (Ahmed 2016; Ang 2013; Natelson 2015; NCT00725101; NCT00793520; NCT01108731; NCT01173055; NCT01234675; NCT01294059; NCT01331109; NCT01621191; Trugman 2014; Ziljstra 2002). One study with desvenlafaxine excluded in the 2013 review, available in clinicaltrials.gov and which did not report data suited for meta-analysis (NCT00369343), was published in a peer-reviewed journal in 2017.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded 22 studies in total: we excluded nine in the 2013 review (Branco 2011; Chappell 2009b; Dwight 1998; Goldenberg 2010; Hsiao 2007; Mease 2010; Saxe 2012; Sayar 2003; NCT00369343) (total corrected in this review), and 13 additional studies for the update (Ahmed 2016; Ang 2013; Natelson 2015; NCT00725101; NCT00793520; NCT01108731; NCT01173055; NCT01234675; NCT01294059; NCT01331109; NCT01621191; Trugman 2014; Ziljstra 2002). One study with desvenlafaxine excluded in the 2013 review, available in clinicaltrials.gov and which did not report data suited for meta-analysis (NCT00369343), was published in a peer-reviewed journal in 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies had fewer than 20 participants per treatment arm (Ahmed 2016; Natelson 2015; NCT00793520; NCT01108731; NCT01234675); 11 studies had no control group (Branco 2011; Chappell 2009b; Dwight 1998;Goldenberg 2010; Hsiao 2007; Mease 2010; NCT00725101; NCT01294059; NCT01331109; NCT01621191; Sayar 2003); two studies did not include outcomes of efficacy, which were preconditions to be included into our review (NCT01173055; Trugman 2014); one study combined milnacipran with education or psychological therapies (Ang 2013); one study duration was shorter than four weeks (Saxe 2012); one study was only published as an abstract (Ziljstra 2002); and for one study the study results were incompletely reported and not suited for quantitative analysis (NCT00369343). …”
Section: Resultsmentioning
confidence: 99%
“…Improvement in the rating of 'being bothered by sleep difficulties' was significant only at week 4 and 8 [55]. A study on milnacipran using polysomnography found that milnacipran did not improve 'wake after sleep onset' or 'number of awakenings after sleep onset' but reduced sleep efficiency [56]. Together these data suggested that SNRI improved sleep by reducing pain rather than having a direct effect on sleep.…”
Section: • Effect Of Snri On Sleepmentioning
confidence: 93%
“…We found 10 clinical trials that evaluated amitriptyline, [34][35][36][37][38][39][40][41][42]67 11 trials that evaluated milnacipran, [57][58][59][60][61][62][63][64][65][66]69 8 trials that evaluated duloxetine, [43][44][45][46][47][48][49][50] and 7 trials that evaluated pregabalin (eTable 2 in the Supplement). [51][52][53][54][55][56]68…”
Section: Characteristics and Risk Of Bias Of The Included Studiesmentioning
confidence: 99%